Differential Diagnosis of Reactive Mesothelial Cells and Adenocarcinoma Cells Using Immunocytochemical markers (Ber-EP 4, MOC-31, Calretinin and HBME-1) in Serous Effusions - Shabbir, Faiza (International Journal of Pathology, 2019)
The inability to undisputedly distinguish reactive mesothelial cells from metastatic adenocarcinoma cells exfoliated in serous effusions is the most common difficulty encountered by pathologists. Ancillary studies are being useful in improving the accuracy of cytological diagnosis. From all the available methods, Immunochemical stains have excelled in the diagnosis of effusion cytology.A combination of epithelial and mesothelial markers is recommended, as use of a single marker alone can’t establish the diagnosis.In present study, we aimed to distinguish adenocarcinoma cells from reactive mesothelial cells with the help of a panel of immunomarkers including; two epithelial cell markers; Ber-EP 4 and MOC 31, and two mesothelial markers; Calretinin and HBME1. Objective: To differentiate reactive mesothelial cells and adenocarcinoma cells by using immunocytochemical markers (Ber-EP 4, MOC-31, Calretinin and HBME-1) in serous effusions. Subjects and Methods: A total 75 fluid samples containing either reactive mesothelial cells or adenocarcinoma were included in the study.Cytospin smears were made and subjected to immunocytochemistry for Ber-EP 4, MOC-31,Calretinin and HBME-1 staining. Results: Ber- EP 4, an epithelial marker, showed positive membranous/cytoplasmic expression in 100% of the effusions which were cytologically diagnosed as positive for adenocarcinoma. MOC 31 expressed diffuse membranous staining in 93% of the total cases of adenocarcinoma.HBME-1 was positively stained in 100% of cases of reactive mesothelial effusions. 100% effusions containing reactive mesothelial cells showed both cytoplasmic and nuclear staining with Calretinin. Conclusion: The immunomarkersBer-EP 4 and Calretinin are more effective in distinguishing reactive mesothelial cells and adenocarcinoma, and they should be included in immunocytochemical (ICC) panel.